Chemistry: a course for 'O' level. workbook - Prescott, Christopher N. (Federal Publications Singapore, 2001)
"Chemistry: A Course for 'O' Level Workbook" is an interactive resource that reinforces chemistry concepts through practical exercises, helping students strengthen their understanding and problem-solving skills in preparation for the O-Level Chemistry exam.